Measurement for accentedness, pause frequency/duration and nuclear stress placement in the EFL classroom - Pedro Luis Luchini (Ilha do Desterro)
This study reports on an experimental research carried out with 50 Spanish-L1 trainees, divided into 2 groups: A & B. Both groups were presented with a traditional-teacher centered approach based on controlled exercises (repetition, imitation), but group B added a communicative component in which students completed a battery of sequenced tasks with a focus on phonological form. Both groups recorded a speaking test before & after instruction which was used to measure and compare degrees of accentedness, frequency & duration of pauses and nuclear stress placement. Ten English-native-speaker-raters judged the recordings to determine the speakers’ degree of perceived accentedness. Two specialists, using inter-marker reliability, segmented the transcriptions of recordings and identified nuclear stress placement. Another two specialists identified empty pauses. Multivariate analysis was used to measure results. Overall, group B (learners exposed to the communicative component) obtained better results in all 3 parameters than the other group. Finally, some pedagogical implications for the teaching of L2 pronunciation in ELT contexts will be discussed.